1995
DOI: 10.1161/01.str.26.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Doppler Microembolic Signal Counts in Patients With Prosthetic Cardiac Valves

Abstract: The detection of microembolic signals in patients with prosthetic cardiac valves is a reproducible technique. The reliable performance of the neuronal network argues for a broader use of this device. The intrasubject stability of the microembolic rate over 1 year supports the concept that the underlying emboligenic process is associated with intrinsic mechanical properties of the valve implant and not due to a thromboembolic process in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
1
13
1
3
Order By: Relevance
“…Obviously, monitoring prosthetic valve carriers immediately after symptom onset would be preferable. Still, the report of Georgiadis et al, 6 who found .insignificant differences in MES counts in 50 patients examined on three different occasions within one year, suggests that the MESgenerating mechanism is stable, and thus the methodology of the present study acceptable.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Obviously, monitoring prosthetic valve carriers immediately after symptom onset would be preferable. Still, the report of Georgiadis et al, 6 who found .insignificant differences in MES counts in 50 patients examined on three different occasions within one year, suggests that the MESgenerating mechanism is stable, and thus the methodology of the present study acceptable.…”
Section: Discussionmentioning
confidence: 48%
“…The resulting use of various Doppler equipment and evaluation of MES counts by more than one observer constitute a weakness of the present study. However, as the interobserver variability in MES counts in patients with prosthetic valves is low, 6 particularly through the high MES intensity in these patients, 7 this limitation is not likely to have greatly influenced our results. monitoring in 79% of cases, and the fact that neurologically symptomatic patients were not routinely monitored over the cerebral vessel supplying the affected territory or immediately after onset of neurological symptoms, constitute further methodological weaknesses.…”
Section: Discussionmentioning
confidence: 89%
“…Transcranial Doppler ultrasonography is able to detect signals representing microemboli in the basal cerebral arteries. [7][8][9][10][11] Recent studies [12][13][14] have shown conspicuously high frequencies of such highintensity transient signals (HITS) in patients with PHV. The debate over whether these HITS are formed elements (eg, platelet aggregates) or gaseous bubbles resulting from cavitation is still not settled, 12,13 and their clinical significance is disputed.…”
mentioning
confidence: 99%
“…This hypothesis is supported by the stable number of MESs found during repeated investigations and the lack of patients' clinical deterioration over time. 6 Also, the rate of cardioembolic stroke in these patients does not appear to be correlated with the number of MESs detected. 15 No correlation could be identified between the patient's hemostaseology and either the number of MESs or the type and extent of antithrombotic treatment.…”
Section: Mess In Prosthetic Heart Valvesmentioning
confidence: 77%